Year prognoses of the alpha acid contents in Czech hops. - Karel KROFTA; Alexandr MIKYŠKA; Jana TICHÁ (Kvasný průmysl, 2012)
A content of alpha acids which is from brewing and commercial point of view, the most important quality parameter of hops, is subjected to distinctive year-to-year fluctuations. It is therefore requires well-timed and reliable information about quality of current crop harvest. Introduced system of alpha acids content evaluation in Czech hops consists of pre-harvest and harvest prognoses and detailed examination of true values. Assessment system is differentiated according to varieties and hop growing regions. This study summarizes the results of year prognoses of alpha acid contents in Czech hops for more than last 15 years. Predicted values compares with true ones and investigates the sources of systematic errors. Pre-harvest prognosis provides early information. The rate of agreement with reality depends primarily on the course of weather conditions before and during the harvest. Prognoses of harvest results are in good compliance with true ones due to relatively high number of evaluated samples (r = 0,986 for Saaz hops in 18 years period). Pre-harvest prognoses for Saaz aroma variety, category VF (virus-free), and hybrid varieties Sládek and Premiant are affected by proportion of samples from young and old plants with very different level of alpha acid contents. Current system of evaluation provides relatively precise information sufficient for the needs of growers, hop processors, merchants and brewers.A content of alpha acids which is from brewing and commercial point of view, the most important quality parameter of hops, is subjected to distinctive year-to-year fluctuations. It is therefore requires well-timed and reliable information about quality of current crop harvest. Introduced system of alpha acids content evaluation in Czech hops consists of pre-harvest and harvest prognoses and detailed examination of true values. Assessment system is differentiated according to varieties and hop growing regions. This study summarizes the results of year prognoses of alpha acid contents in Czech hops for more than last 15 years. Predicted values compares with true ones and investigates the sources of systematic errors. Pre-harvest prognosis provides early information. The rate of agreement with reality depends primarily on the course of weather conditions before and during the harvest. Prognoses of harvest results are in good compliance with true ones due to relatively high number of evaluated samples (r = 0,986 for Saaz hops in 18 years period). Pre-harvest prognoses for Saaz aroma variety, category VF (virus-free), and hybrid varieties Sládek and Premiant are affected by proportion of samples from young and old plants with very different level of alpha acid contents. Current system of evaluation provides relatively precise information sufficient for the needs of growers, hop processors, merchants and brewers.